Hangary`s and Romania`s exogenous influence on separatism processes in Ukraine - Ryabinin, Yevgeny (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author, on the basis of a preliminary analysis of the problem of the exogenous influence of the countries on the strengthening of separatism processes in Ukraine, expresses the view that separatism conflicts have not only internal causes for escalation, but also the external influence exerted by the main actors of international relations, solving their geopolitical task or countries bordering Ukraine. The author classifies the exogenous factors of influence, which are most often used by the main and influential actors of international relations to strengthen their positions in the region or in any state.
Keywords: Transcarpathia; separatism; exogenous factors; Ukraine; Hungary; Romania